Relatório de Estágio Profissional - Desafio Cruzado: Do desconforto inicial à confiança e antecipação a ensinar Educação Física - Pedro Filipe Pereira Gomes (2018)
The following report entails two purposes: whilst contending to be a first-person account of the entire student teaching process, it is equally intended to serve as a lattermost tool capable of forming insights and knowledge for the author as a future teacher of PE (Physical Education).The document exerts a description of a personal experience - it accounts the main hardships, frustrations and accomplishments achieved in the course of a professional practicum in PE carried out in a public educational institution.The practicum report will be apportioned in five major parts: The first part entails the display of the introduction of the document's main aspects.The second part, farther directed to the necessity of PE as a subject in the curricular plans, will ensemble the portrayal and characterization of the professional student teaching and its importance for the intern, followed by the description of the context of action as a highly influential element of the totality of the experience. The third part of this report will refer to all practical experiences in the context of the practicum, purposely everything that helped convey the teaching-learning process (conceptualization, planning, accomplishment and evaluation) as well as all the activities that were developed beyond the mandatory curriculum that inevitably contributed to my development as a future teacher.It will also be in this part of the report that the results of the sociometric study of the class, prepared by the trainee student, will be presented. This study has proven to be an excellent tool for the cognizance of the group and the consequent improvement of the teaching-learning process.This will be followed by final considerations concerning all the experiences that I went through as well as my perspective on my professional development and the construction of my identity as a teacher.